Takotsubo cardiomyopathy triggered by wasabi consumption: can sushi break your heart? - Finkel-Oron, Alona (BMJ Case Rep, 2019)
Takotsubo cardiomyopathy is a left ventricular dysfunction that typically occurs after sudden intense emotional or physical stress and mimics myocardial infarction. We describe a case of a 60-year-old woman that presented to the emergency department with chest pain after she attended a wedding and ate a large amount of wasabi, assuming it to be an avocado. To the best of our knowledge, this is the first report of takotsubo cardiomyopathy triggered by wasabi consumption.